2008
DOI: 10.1093/geronb/63.1.s25
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Influences on Cognitive Impairment Among Oldest Old Chinese

Abstract: Our findings suggest that socioeconomic environment throughout the life course, early life in particular, can influence the risk of cognitive impairment in old age. Not only can public policy that targets illiteracy, hunger, and poverty improve the lives of tens of thousands of children, but ultimately such investments will pay significant dividends many decades later in enhancing the cognitive well-being of older persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
148
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(183 citation statements)
references
References 38 publications
20
148
2
1
Order By: Relevance
“…However, this study showed that wealth played a minor role in affecting the examined cognitive tasks of individuals, while education was a significant protective factor to prevent cognitive decline in aging. This result is in line with other studies (Le Carret et al 2003;Zhang et al 2008;Adam et al 2013) which suggest that education represents one of the most important factors that contribute to the development of cognitive reserve.…”
Section: Discussionsupporting
confidence: 93%
“…However, this study showed that wealth played a minor role in affecting the examined cognitive tasks of individuals, while education was a significant protective factor to prevent cognitive decline in aging. This result is in line with other studies (Le Carret et al 2003;Zhang et al 2008;Adam et al 2013) which suggest that education represents one of the most important factors that contribute to the development of cognitive reserve.…”
Section: Discussionsupporting
confidence: 93%
“…Presence of chronic conditions is indicated by the respondent's reporting to have one or more of five main non-communicable diseases: hypertension, diabetes, heart disease, stroke-related conditions, and respiratory-related diseases. Cognitive impairment is measured as a dichotomized variable (impaired vs. unimpaired) using the well-validated Chinese version of the Mini-Mental State examination (MMSe) (Zhang et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Next to showing a consistently negative correlation between low early-life SES and self-rated health in adulthood, studies also revealed a significant relationship between childhood SES and older adults' risk of suffering from functional limitations (e.g., Haas 2008;Huang et al 2011;Wen and Gu 2011), cognitive impairment (e.g., Wen and Gu 2011;Zhang et al 2008), as well as chronic conditions and depressive symptoms (e.g., Luo and Waite 2005;Pavela and Latham 2016). Along the same lines, poor childhood health was shown to have long-term negative effects on, for example, individuals' functional status (e.g., Haas 2008;Huang et al 2011) and chronic health conditions (e.g., Blackwell et al 2001;Haas 2007).…”
mentioning
confidence: 96%
“…On one hand, early nutritional deprivation, for example, might directly initiate negative health trajectories during the individual's childhood, which may persist or even aggravate during the ageing process, independent of adult SES ('latency model'; e.g., Huang et al 2011;Zhang et al 2008). On the other hand, poor health and economic deprivation in childhood might impact later life health indirectly through impaired adult socioeconomic attainment ('pathway model'; e.g., Case et al 2005;Haas 2008).…”
mentioning
confidence: 99%